Modeling Business Student Satisfaction: Utilitarian Value and Hedonic Value as Drivers of Satisfaction. Issue 4 (1st October 2020) - Arizzi, Gabriella; Breitenreiter, Jake; Khalsa, Ronan; Iyer, Rajesh; Babin, Laurie A.; Griffin, Mitch
ABSTRACT: With changing demographics and the potential impact of COVID-19 on enrollment, understanding student satisfaction, student retention, and willingness to recommend a university to prospective students is critically important. Based on a survey of business school students from two universities, this paper illustrates the impact of utilitarian and hedonic value as drivers of student satisfaction. In turn, satisfaction is shown to heavily influence student intentions to remain at the current school, as well as recommend that school to others. The student's year in college is found to moderate the relationship between utilitarian and hedonic values and student satisfaction.